2006
DOI: 10.1051/0004-6361:200600017
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRAL observations of the blazar 3C 454.3 in outburst

Abstract: In Spring 2005, the blazar 3C 454.3 underwent a dramatic outburst at all wavelengths from mm to X-rays. This prompted INTEGRAL observations, accomplished in 15−18 May 2005. The source was detected by the INTEGRAL instruments from 3 to 200 keV in a bright state (∼5 × 10 −10 erg s −1 cm −2 ), at least a factor of 2−3 higher than previously observed. This is one of the brightest blazar detections achieved by INTEGRAL. During the 2.5 days of INTEGRAL monitoring, we detected a ∼20% decrease in the hard X-rays (20−4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 38 publications
2
103
0
Order By: Relevance
“…In 2005 it underwent a very active phase in optical and X-ray bands, triggering intensive observations in the radio, optical and X-ray (Swift, Chandra, INTEGRAL) bands (Villata et al 2006;Giommi et al 2006;Pian et al 2006). Unfortunately no γ-ray satellite was operating in the GeV domain at that time and no information was obtained in that band.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…In 2005 it underwent a very active phase in optical and X-ray bands, triggering intensive observations in the radio, optical and X-ray (Swift, Chandra, INTEGRAL) bands (Villata et al 2006;Giommi et al 2006;Pian et al 2006). Unfortunately no γ-ray satellite was operating in the GeV domain at that time and no information was obtained in that band.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…See McHardy (2010) for a review of X-ray variability and its scaling from stellar to super-massive black holes. On the other hand, the large majority of the hard X-ray variability studies performed in the last years focused on the spectral variability of AGN at different flux levels for single bright sources or for small samples of selected objects, thanks to pointed observations of the BeppoSAX (e.g., Petrucci et al 2000;Nicastro et al 2000;de Rosa et al 2007), INTEGRAL (e.g., Pian et al 2006Pian et al , 2011Beckmann et al 2008;Lubiński et al 2010;Soldi et al 2011a;Petrucci et al 2013) and Suzaku (e.g., Reeves et al 2007;Itoh et al 2008;Terashima et al 2009;Fukazawa et al 2011;Reis et al 2012) satellites. These X-ray studies suggest different origins for the observed variability, such as changes in the amount of absorption or of its ionization, fluctuations in the seed photon flux, intrinsic modifications of the corona properties or geometry (or of the jet parameters, in case of radio loud AGN), or a variable contribution of different spectral components, with at least some of these scenarios driven by accretion rate variations.…”
Section: Introductionmentioning
confidence: 99%
“…Dermer et al 2009, and references therein). The quasar-type blazar 3C 454.3 has received particular attention by the international astronomical community since it underwent a major outburst in 2005 (Villata et al 2006;Giommi et al 2006;Pian et al 2006;Fuhrmann et al 2006). Indeed, A&A 534, A87 (2011) after many decades of intense radio, but only mild optical activity, the source began brightening in the optical band in 2001, until in May 2005 it reached the maximum optical level ever observed, R = 12.0.…”
Section: Introductionmentioning
confidence: 99%